Organized crime from the Mob to transnational organized crime - Albanese, Jay S. (Routledge, 2015)
This book offers a comprehensive survey, including an extensive history of the Mafia in the United States; a legal analysis of the offenses that underlie organized crimes; specific attention to modern manifestations of organized crime activity, such as human smuggling, Internet crimes, and other transnational criminal operations; and the application of ethics to the study of organized crime